UPAYA MENINGKATKAN HASIL PEMBELAJARAN IPS MELALUI PENERAPAN MODEL GRUP INVESTIGATION SISWA KELAS V SDN 1 TALANG TELUK BETUNG SELATAN BANDAR LAMPUNG - Helnawati, Helnawati (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The purpose of this study was to improve the quality of social studies learning through the Group Investigation model in class V SDN 1 Talang Teluk Betung Selatan Bandar Lampung. To achieve the research objectives mentioned above, the author uses the research method "Classroom Action Research" which is abbreviated as CAR or classroom action research (PTK). Classroom action research (CAR) is action research carried out by teachers in the classroom. This model uses a self-reflection spiral system starting from planning, action, observation, reflection, and re-planning which is the basis for a problem-solving design. And use an integrated approach in learning. The research design used two cycles, each cycle consisting of two meetings and four stages, namely planning, implementing, observing, and reflecting. The research subjects were fifth grade students of SDN 1 Talang Teluk Betung Selatan Bandar Lampung. Data collection techniques using observation and tests. Based on the results of the study, it can be concluded that there is an increase in the learning activities of SDN 1 Talang class V students after the Group Investigation learning model is applied in social studies learning, this can be seen in the initial condition that the average score is 51 with the highest score of 70. In cycle I, the average score -Average 54.07 with the highest score of 90. In cycle II the average score was 76.26 with a high value of 100. Completeness of learning has increased, in the initial conditions, learning completeness was 45.8%, in cycle I it increased to 72, 9% and in the second cycle to 89.6%